MORE COMMENTS BY HENRI HERZ ON MUSICAL TASTE IN NINETEENTH CENTURY AMERICA - Hill, Henry Bertram; Gara, Larry (American Studies, 1961)
MORE COMMENTS BY HENRI HERZ ON MUSICAL TASTE IN NINETEENTH CENTURY AMERICA